THE STUDY ON THE EFFICACY OF SUKOSHNA (LUKE WARM) YASHTIMADHU GHRITA IN THE MANAGEMENT OF PAIN DURING APPLICATION OF KSHARASUTRA IN BHAGANDARA (FISTULA IN ANO) (AYUSHDHARA, 2018)
Bhagandara is one of the oldest diseases which have been described as one of the Ashta Mahagadas  (Eight grave disorders). Ksharasutra application is a successful method and is one of the chief modalities described for the treatment of Bhagandara in Ayurvedic texts. The local cauterizing pain and prolonged period of treatment causes the agony in few patients and make them to avoid undergoing Ksharasutra application. The ability to alleviate pain is one of the most noteworthy goals during change of Ksharasutra in  Bhagandara. The conventional use of 2% xylocaine jelly before changing Ksharasutra had local anaesthetic effect up to limited time and also didn’t have any other advantages like healing of fistula.30 patients with signs and symptoms of Bhagandara who are treated with Ksharasutra were selected by simple random sampling method. Apamarga Ksharasutra and Yastimadhu Ghrita were prepared as per the standard method described in Ayurvedic texts. In the present trial 4 sittings were taken into study and in the 1st sitting 2% xylocaine jelly was applied and in the next three sittings, Sukoshna (Luke warm) Yastimadhu Ghrita was applied to find out its effectiveness in the management of pain during Ksharasutra therapy by comparing 1st and Last sitting. Lastly, it was concluded that the present study was efficacious and non-invasive and it was found to be statistically highly significant in alleviating pain, burning sensation and PRD during and after application of Ksharasutra without any side effect.